Efektifitas Terapi Pijat Laktasi Oksitosin dan Akupresur Titik Zhongfu terhadap Produksi ASI pada Ibu Post Partum - Dian Puspita Yani; Sri Banun Titi Istiqomah; Arifah Retnowuni (STIKES Karya Husada Kediri, 2022)
Breastfeeding phase is a very important process for mothers who have just given birth since breastfeeding is very supportive of the growth and development of the baby. It is a challenge for a mother who prefers to give up because breast milk is not smooth so that the baby does not get exclusive breast milk within the first 6 months of his/her life. Acupressure is used as an alternative to increase breast milk production during the postpartum period. The aim of this study is to analyze the effectiveness of oxytocin lactation therapy and zhoungfu point acupressure (LU-1) to breast milk production in postpartum mothers at CBA SPA Sumobito Jombang in 2021. This research method uses pre-experimental design experiments with one group uses pre and post-test. There are two variable, that is one independent variable on oxytocin lactation massage therapy and zhoungfu point acupressure and the dependent variable on milk production. The sample was postpartum mothers who breastfed their babies as many as 20 of them were given a treatment of 10 people with oxytocin lactation massage therapy and 10 acupressure therapy at the point of zhoungfu (LU-1). It needs 30 minutes for 3 days. To assess the production of breast milk is done a smooth and uneventful assessment on the 4th day of massage therapy. Data was analyzed using Wilcoxon signed-rank test data analysis. The results of the Wilcoxon signed-rank test using SPSS program were obtained that the result of oxytocin lactation massage therapy with a value of 0.008 (p-value < 0.05) while the results of acupressure massage therapy at the zhoungdu point (LU-1) were obtained p-value 0.005 (p-value < 0.05). There is a difference between oxytocin lactation massage therapy and acupressure at zhoungfu (LU-1). This study concludes that there is a significant difference between oxytocin lactation massage therapy and zhoungfu point acupressure (LU-1). Keywords: Oxytocin Lactation Massage, Zhoungfu Point Acupressure (LU-1), Breast Milk Production